(untitled) (Texas Journal of Philology, Culture and History, 2022)
In this article, in the analysis of the linguistic and cultural aspects of Uzbek and English proverbs, we describe the interdependence of language and culture, consider the thematic similarities of Uzbek and English proverbs, and the expression of mentality and national character in them. we will try to take a deeper approach to such issues.